Desenvolvimento de adsorventes de nanofibras de quitosana/nylon 6 e tanino/nylon 6 por Forcespinning para remoção de cromo em meio aquoso - Kummer, Gislaine (2017)
New nanofiber materials composed of chitosan/nylon 6 and tannin/nylon 6 were prepared by the Forcespinning method and were used as adsorbents for the removal of chromium VI from aqueous solutions. Under optimum experimental conditions, the nanofibers showed similar production rates of 3.5 g h-1. The diameters of the nanofibers ranged from 100 to 800 nm. The adsorption of chromium VI was favored at pH 3 (chitosan/nylon 6 nanofibers) and pH 2 (tannin/nylon 6 nanofibers) and a temperature of 328 K. The most suitable models for description of the kinetic data were the pseudo-second order model (chitosan/nylon 6 nanofibers) and the Elovich model (tannin/nylon 6 nanofibers). For both nanofibers, the equilibrium isotherms could be fitted by the Langmuir model. The maximum adsorption capacities were 23.9 and 62.7 mg g-1 for the chitosan/nylon 6 and tannin/nylon 6 nanofibers, respectively. The thermodynamic parameters showed that the adsorption was spontaneous, favorable, and endothermic. The findings indicated that these nanofibers produced using a centrifugal technique offer excellent potential as adsorbents, with high adsorption capacities for chromium VI.